PENGENALAN PERANCANGAN SISTEM INFORMASI TEKNOLOGI BERDASARKAN INSPIRASI KARYA ALLAH DALAM MENDESAIN ALAM SEMESTA - Anggraeni, Dewi; Maharani, Dewi; Harahap, Indra Ramadona; Rizaldi, Rizaldi (Smart Education, 2025)
Abstract: Community service is part of the implementation of the Tri Dharma of Higher Education, which emphasizes the importance of academic contributions in empowering the community. In the rapidly evolving technological era today, one of the main solutions to reduce the digital divide in society is through education and assistance related to the use of information technology. Therefore, this activity raises the theme 'Introduction to Designing Information Technology Systems Based on the Inspiration of God's Works in Designing the Universe'. Community service is part of the implementation of the Tri Dharma of Higher Education, which emphasizes the importance of academic contributions in empowering the community. In the era of rapidly advancing technology today, one of the main solutions to reduce the digital divide in society is through education and assistance related to the use of information technology. Therefore, this activity raises the theme 'Introduction to Designing Information Technology Systems Based on the Inspiration of God's Works in Designing the Universe.' Keywords: Information Technology; Natural Design; Work Inspiration Abstrak: Pengabdian kepada masyarakat merupakan bagian dari implementasi Tri Dharma Perguruan Tinggi, yang menekankan pentingnya kontribusi akademisi dalam memberdayakan masyarakat. Dalam era teknologi yang berkembang pesat saat ini, salah satu solusi utama untuk mengurangi kesenjangan digital di masyarakat adalah melalui edukasi dan pendampingan terkait pemanfaatan teknologi informasi. Oleh karena itu, kegiatan ini mengangkat tema “Pengenalan Perancangan Sistem Informasi Teknologi Berdasarkan Inspirasi Karya Allah dalam Mendesain Alam Semesta”. Pengabdian kepada masyarakat merupakan bagian dari implementasi Tri Dharma Perguruan Tinggi, yang menekankan pentingnya kontribusi akademisi dalam memberdayakan masyarakat. Dalam era teknologi yang berkembang pesat saat ini, salah satu solusi utama untuk mengurangi kesenjangan digital di masyarakat adalah melalui edukasi dan pendampingan terkait pemanfaatan teknologi informasi. Oleh karena itu, kegiatan ini mengangkat tema “Pengenalan Perancangan Sistem Informasi Teknologi Berdasarkan Inspirasi Karya Allah dalam Mendesain Alam Semesta.” Kata kunci: Information Technology; Natural Design; Work Inspiration